Application of aromatherapy in patients with cognitive impairment: An integrative review - Die Xing; Xin Chen; Yu Ma; Mengmeng Chen; Mei Fung Ho; Kylie Ka Yee Lam; Ying Zhou; Thomas Kwok Shing Wong (Journal of Integrative Nursing)
This integrative review examines the therapeutic applications of aromatherapy in cognitive impairment spectrum disorders, spanning from subjective cognitive decline to dementia. A comprehensive search across twelve databases (PubMed, Web of Science, Embase, Cochrane Library, Scopus, OVID, EBSCOhost, ProQuest, CNKI, WF, VIP, and CBM) identified 28 studies up to March 2024, analyzed through Whittemore and Knafl’s five-stage framework with mixed methods appraisal tool (MMAT) quality appraisal and Template for Intervention Description and Replication -guided data extraction. Three primary intervention modalities emerged: inhalation (most prevalent), massage, and combined approaches, employing diverse essential oils with variations in dosage, administration timing, and environmental contexts. Outcome assessments covered cognitive performance, neuropsychiatric symptoms, functional abilities, quality of life metrics, caregiver impacts, and safety profiles. When demonstrating therapeutic potential, significant heterogeneity in essential oil selection (types and concentrations) and intervention protocols hindered comparative analysis. Future research should focus on understanding the compositions of essential oils to establish appropriate applications and dosage guidelines. In addition, more reliable information on safe inhalation methods is necessary, alongside the exploration of traditional Chinese medicine essential oils to enhance aromatherapy practices. High-quality randomized controlled trials are essential to assess the effectiveness and safety of aromatherapy in this context.